Analysis of Online Rating and Online Review on Hotel Buying Interest - Annisa Nurfitriani; Yulia Nur Hasanah (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2022)
This research is motivated by the decreased room occupancy rates in Indonesia due to the COVID-19 pandemic, where the hotel industry is one of the major industries in this country. With this pandemic, people have new considerations in choosing hotels by tending to look for information on the internet. Therefore, this research aims to analyze the effect of online ratings and online reviews on hotel buying interest. The data on this research were collected by distributing a questionnaire to 100 respondents. In determining the sample, the technique used is purposive sampling which is included in the non-probability sampling category. The research method is quantitative and the analytical method used in this research is multiple linear regression analysis, which is processed using the software SPSS. The results showed that online ratings and online reviews have a positive and significant effect on hotel buying interest partially and simultaneously.